Application of real options valuation in nuclear energy systems - Abdollah Arasteh (International Journal of Research in Industrial Engineering)
In recent years, there has been a very increasing trend in energy consumption worldwide, especially in the electricity sector, which, due to global sensitivities to protecting the environment and reducing greenhouse gas emissions, leads to the use of other non-fossil sources of electricity generation, such as renewable energy (wind, hydropower and solar) as well as nuclear energy. Nuclear power has been re-evaluated as a viable alternative to fossil fuels due to growing energy costs, climate change, and concerns about supply security. The present implementation of economies of scale has led to the development of a Light Water Reactor (LWR) design that lacks the ability to assess the strategic advantage and economic potential of contemporary nuclear systems. Real options analysis and portfolio theory are used to diversify and modify nuclear investments. According to this study, a single investor may make better selections for efficient and mindful nuclear energy development. The nuclear power industry received special attention. Multiple commercial and technology problems face huge, irrevocable investments. The fuel cycle's front and rear ends provide versatility. By leveraging the fuel cycle, many nuclear energy alternatives have the potential to provide economic benefits, hence expediting the shift towards more environmentally friendly energy usage. A wide range of operational and strategic considerations need the expanding use of mathematical models to help decision-making.